Patient representatives: Crucial members of health‐care working groups facing an uncertain role and conflicting expectations. A qualitative study - Anna Hult; Ewa Lundgren; Eva Jangland (Wiley, 2021)
Abstract Background Patient representatives (PRs) have been involved for decades in health‐care development, and their participation is increasingly sought in health‐care working groups (HCWGs) on every level. However, information on how the role could be further developed and teamwork improved remains sparse. Objective To explore the role of patient representatives in clinical practice guideline (CPG) monitoring groups, to describe their contributions and identify possibilities of improvement. Design Qualitative design using semi‐structured interviews analysed by content analysis. Setting and participants Interviews were conducted with 11 PRs, 13 registered nurses, and 9 physicians, all members of national committees monitoring CPGs for cancer in Sweden. Results Most participants considered the PR role important but mentioned several problems. PRs' contributions were hampered by uncertainties about their role, the low expectations of other group members and their sense that their contributions were often disregarded. Some professionals questioned whether PRs were truly representative and said some topics could not be discussed with PRs present. Conclusion This study highlights the fundamental problems that remain to be solved despite the long involvement of PRs in HCWGs. Even though the PR role and teamwork differed between the groups, most PRs need to be empowered to be actively involved in the teamwork and have their engagement and knowledge fully utilized. Enhancing teamwork through clarifying roles and expectations could lead to more inclusive and equal teams able to work more effectively towards the goal of improving health care. Patient or public contribution PRs were information givers in data collection.